2019
DOI: 10.3390/ani9121123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Energy on Growth Performance, Rumen Fermentation and Bacterial Community, and Meat Quality of Holstein-Friesians Bulls Slaughtered at Different Ages

Abstract: The objective of this study was to evaluate the effects of dietary energy levels on growth performance, rumen fermentation and bacterial community, and meat quality of Holstein-Friesians bulls slaughtered at different ages. Thirty-six Holstein-Friesians bulls (17 months of age) were divided into a 3 × 3 factorial experiment with three energy levels (LE, ME and HE; metabolizable energy is 10.12, 10.90 and 11.68 MJ/kg, respectively) of diets, and three slaughter ages (20, 23 and 26 months). Results indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 46 publications
(49 reference statements)
13
18
0
Order By: Relevance
“…In this study, at the age of 20 months, bulls in the LE group had higher IGF1 expressions than those in the ME and HE groups; at the age of 26 months, bull in the LE group had lower IGF1 expressions than those in the ME group. Consistent with those results, we previously observed that the average daily gains were similar at the age of 20 months, whereas increased at the age of 23 and 26 months (Wang, Li et al., 2019). Serum cholesterol is a predictor of energy balance status in cattle (Kim & Lee, 2003).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, at the age of 20 months, bulls in the LE group had higher IGF1 expressions than those in the ME and HE groups; at the age of 26 months, bull in the LE group had lower IGF1 expressions than those in the ME group. Consistent with those results, we previously observed that the average daily gains were similar at the age of 20 months, whereas increased at the age of 23 and 26 months (Wang, Li et al., 2019). Serum cholesterol is a predictor of energy balance status in cattle (Kim & Lee, 2003).…”
Section: Discussionsupporting
confidence: 89%
“…The bulls were randomly allocated into three diet treatments, and diets were designed according to the nutrient requirements of beef cattle (NRC, 2016) to achieve metabolizable energy contents of 10.12 (low energy, LE), 10.90 (medium energy, ME) and 11.68 (high energy, HE) MJ/kg. Bulls were individually fed the total mixed rations at 07:00 and 16:30, and the dry matter intake was reported in our previous research (Wang, Li et al., 2019). The dietary ingredients and nutrient composition are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that dietary nutrients play a pivotal role in regulating the meat composition of livestock. For instance, increased dietary energy increased the content of intramuscular fat of Holstein-Friesians bulls [42]. Moreover, dietary supplementation with sea buckthorn pomace increased the crude fat content of lambs, but had no significant influence on other nutrient contents [43].…”
Section: Meat Compositionmentioning
confidence: 98%
“…In this study, the decreasing length of roughage increased the abundance of Pyramidobacter , suggesting that chopping roughage length is beneficial to the health of weaned calves. In addition, our results showed that decreasing the length of roughage increased the abundances of genera Papillibacter and Eubacterium_hallii_group , whose abundances affect butyrate production in the rumen [ 45 , 46 , 47 ], indicating that chopping roughage altered the rumen bacterial community and promoted the development of the rumen.…”
Section: Discussionmentioning
confidence: 98%